Preparation of BST Powders and Ceramics via a Hybrid Method - Klaytae, Thanawat; Vittayakorn, Naratip; Sumang, Rattiphorn (My University, 2023)
Barium strontium titanate (Ba0.8Sr0.2TiO3; BST) ceramics, were prepared by the hybrid method between Solid-state reaction (SSR) and Sol-gel methods (SG) in a ratio of 1:0.1–1:0.5. The BST powder was successfully calcined at 850 °C for 2 h. This temperature is much lower than the calcination temperatures of the SSR method. The BST ceramics were sintered between 1150 and 1450 °C. All samples showed the pure perovskite structure corresponding to JCPDS no. 34-0411. The optimum sintering temperature was observed from the samples sintered at 1450 °C for 4 h, indicating a density of 5.26 g/cm3, dielectric constant of 7018, and ferroelectric properties: (P max = 13.8 μC/cm2, P r = 2.5 μC/cm2 and E c = 2.3 kV/cm at 30 kV/cm).
Keywords: ferroelectric; hybrid method; microstructure; Phase transition